ATM 2016
DOI: 10.20937/atm.2016.29.03.05
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Loop Current metrics and eddy detachments to different model configurations: The impact of topography and Caribbean perturbations

Abstract: RESUMENLa dinámica de la Corriente del Lazo (LC, por sus siglas en inglés) y la separación de su remolino anticiclónico (LCE, por sus siglas en inglés) son algunas de las características más importantes de la circulación en el Golfo de México (GoM, por sus siglas en inglés), así como índices comunes para evaluar la validez de las simulaciones numéricas. Utilizando un modelo numérico se estudian la sensibilidad de la LC y las separaciones de los LCE ante tres diferentes mecanismos considerados relevantes para s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 45 publications
1
21
0
Order By: Relevance
“…4c) related to barotropic instabilities can be observed in the area of the LC from the Yucatan channel up to its tip. Similar results were also simulated by Garcia-Jove et al (2016). Another noticeable color in Fig.…”
Section: ) Eke Generation and Dissipationsupporting
confidence: 86%
“…4c) related to barotropic instabilities can be observed in the area of the LC from the Yucatan channel up to its tip. Similar results were also simulated by Garcia-Jove et al (2016). Another noticeable color in Fig.…”
Section: ) Eke Generation and Dissipationsupporting
confidence: 86%
“…Zavala‐Hidalgo et al () also found a relationship between the generation of the LCFE and LC dynamics; the cyclones observed on the northeast shelf break of the Campeche Bank during 1993–2000 were generated during the last stage of the LC shedding. Garcia‐Jove et al () also observed an increase in eddy KE associated with the generation and intensification of the frontal eddies during the extended stages of the LC. Therefore, not only the formation but also the later intensification of the LCFEs is dependent on the stage of the LC.…”
Section: Resultsmentioning
confidence: 88%
“…Even though the LC is losing total APE through baroclinic instability (Donohue, Watts, Hamilton, Leben, & Kennelly, ), locally, the growth of the LCFEs strengthens the LC front (Figures and ), enhances the density gradients (Figure ), and drives a local increase in APE in the LC (Figure ). In fact, Garcia‐Jove et al () showed, using numerical models, that eddies can transfer energy to the mean LC, especially on the eastern flank of the LC.…”
Section: Resultsmentioning
confidence: 99%
“…The circulation fields (temperature, salinity, currents, diffusivity) have been obtained using a GoM regional configuration based on the Nucleus for European Modelling of the Ocean (NEMO), a state-of-the-art modeling environment of ocean related engines (Madec 2016). The configuration that we employed, called GOLFO12, is described in detail in Damien et al (2018) and similar to the one used in Garcia-Jove Navarro et al (2016). The resolution is 1/12°degree in longitude and latitude.…”
Section: Modeling Framework and Methodologymentioning
confidence: 99%